A Bahasa Inggris - Datice Anurahman; Bambang Agus Pramuka; Negina Kencono Putri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2023)
Indonesia has 235.53 million Muslim population, making up 86.88% of the country's total population. In this regard, an online zakat financial instrument is helpful to ensure equal income and alleviate poverty. This study aims to examine the effectiveness of electronic zakat payment and the factors optimizing the electronic zakat payment. This systematic literature review examines articles in a structured and systematic manner. The data sources of the study were secondary data obtained from several previous studies. The study found that online zakat payment has not been conclusive due to several factors, including an overly high target, lack of socialization on technology use, and the absence of sharia regulation. Electronic zakat distribution could be more effective if more people adopt this transaction method.